PENINGKATAN PERTUMBUHAN TANAMAN PADI PADA TANAH SALIN-SODIK MELALUI APLIKASI AMANDEMEN GIPSUM DAN AMANDEMEN BIOCHAR SEKAM PADI-KOTORAN SAPI SERTA MELALUI BIOPRIMING BENIH DENGAN PSEUDOMONAS AERUGINOSA DAN AZOTOBACTER CHROOCOCCUM - Magdalena, Imelda
Due to crop depletion and increase in population, the world is reported to be facing a food crisis today. The most significant factor influencing this trend is the deterioration of soil quality as a result of soil salinity and sodicity. This situation will cause the soil's physicochemical qualities to deteriorate, restricting water and nutrient absorption and impeding plant growth. Although leaching can help reduce salt concentration, this method consumes a lot of water and can leached off important soil material. Soil amendments are reported to aid in the efficient leaching process and provide nutrients that can regulate plant growth. Another approach is to increase salt tolerance in plant by injecting plant growth promoting rhizobacteria (PGPR) into seedlings. The purpose of this study is to examine the characteristics of salt-induced soil after reclamation using various amendments such as organic amendments, inorganic amendments, and seed inoculation with the PGPR consortium, as well as the effect on the increase in rice plant growth and yield. The experiment began by watering the alluvial clay soil with a 3.5 % salt solution to create saline-sodic soil. The salt-induced soil is then amended with cow dung-biochar (BK), 100% gypsum (G100), 80% gypsum (G80), 40% gypsum (G40), 20% gypsum (G20), 10% gypsum (G10) of the stoichiometry gypsum required, and without such additions as control (K). The addition of these amendments is followed by a 40-day leaching period, after which the physicochemical properties of soil are examined before these soils were used as growing medium for the rice plant. The biopriming approach was used to inoculate rice seedlings with PGPR. The impact of biopriming on physicochemical of the soil as well as on rice plant growth is investigated using the soil with no addition of the amendments (P). A combination of Pseudomonas aeruginosa and Azotobacter chroococcum was employed in this investigation as PGPR. Rice plant growth was monitored for 112 days till harvest. The addition of the amendments gives a prominent influence on the decrease of salinity, according to this study. The G100 variant shows a significant impact on the soil's chemical features, including a 75% reduction in EC, a 77% decrease in Na+, a 55% increase in Ca2+, reduction of pH value to 5.6, a 93% decrease in ESP, and a 94% decrease in ESP. Variant BK shows greatest physical properties of soil, with a lower density (0.865 g/cm3) and a higher water retention capacity (85%) than the optimal value. The variant P produced the greatest outcomes in terms of rice plant growth and yield. In comparison to other variants, this variation produced the highest output of height (74,5 ± 6,9 cm), tiller number (30 ± 4/plant), root length (17,4 ± 3,6), number of leaves (70 ± 11/plant), chlorophyll value (2,49 ± 0,18 mg/g), biomass weight (61,77 ± 0,19 g), and yield (4,0 1± 0,2 g).